Assessment of chosen technologies improving seniors' quality of life in the context of sustainable development - Halicka, Katarzyna (Technological and Economic Development of Economy, 2024)
Sustainable development is a perspective on economic progress that takes into account the equilibrium among social, economic, and environmental elements. This implies that endeavours aimed at development should guarantee the satisfaction of present generations’ requirements while safeguarding the capacity of future generations to fulfil their own necessities. In the context of an aging society, sustainable development involves providing solutions, services, and technologies that address the needs of older people while also minimizing negative impacts on the environment and future generations. The aim of this article is to identify, analyse and evaluate technologies that improve the quality of life of older people without compromising the well-being of future generations from ecological, social, ethical and other perspectives. Technologies that enhance the quality of life for older people are often referred to as gerontechnologies in the literature.The article identifies and then selects 3 gerontechnologies that can improve the quality of life of older people while remaining sustainable. Further, 42 criteria for evaluating gerontechnologies were identified. These gerontechnologies were then evaluated by potential users. A ranking of gerontechnologies was further developed. CAWI and CATI methods were used in the survey. The SAW method was used to build the ranking.